Cardiovascular Outcomes in Relation to Antihypertensive Medication Use in Women with and Without Cancer: Results from the Women's Health Initiative. (6th April 2020) - Reding, Kerryn W.; Aragaki, Aaron K.; Cheng, Richard K.; Barac, Ana; Wassertheil‐Smoller, Sylvia; Chubak, Jessica; Limacher, Marian C.; Hundley, W. Gregory; D'Agostino, Ralph; Vitolins, Mara Z.; Brasky, Theodore M.; Habel, Laurel A.; et al.
Abstract: Background: Recent clinical trials have evaluated angiotensin‐converting enzyme (ACE) inhibitors (ACEis), angiotensin receptor blockers (ARBs), and beta blockers (BBs) in relation to cardiotoxicity in patients with cancer, typically defined by ejection fraction declines. However, these trials have not examined long‐term, hard clinical endpoints. Within a prospective study, we examined the risk of heart failure (HF) and coronary heart disease (CHD) events in relation to use of commonly used antihypertensive medications, including ACEis/ARBs, BBs, calcium channel blockers (CCB), and diuretics, comparing women with and without cancer. Materials and Methods: In a cohort of 56, 997 Women's Health Initiative study participants free of cardiovascular disease who received antihypertensive treatment, we used multivariable‐adjusted Cox regression models to calculate the hazard ratios (HRs) of developing CHD, HF, and a composite outcome of cardiac events (combining CHD and HF) in relation to use of ACEis/ARBs, CCBs, or diuretics versus BBs, separately in women with and without cancer. Results: Whereas there was no difference in risk of cardiac events comparing ACEi/ARB with BB use among cancer‐free women (HR = 0.99 [0.88–1.12]), among cancer survivors ACEi/ARB users were at a 2.24‐fold risk of total cardiac events (1.18–4.24); p ‐interaction = .06). When investigated in relation to CHD only, an increased risk was similarly observed in ACEi/ARB versus BB use for cancer survivors (HR = 1.87 [0.88–3.95]) but not in cancer‐free women (HR = 0.91 [0.79–1.06]; p ‐interaction = .04). A similar pattern was also seen in relation to HF but did not reach statistical significance ( p ‐interaction = .23). Conclusion: These results from this observational study suggest differing risks of cardiac events in relation to antihypertensive medications depending on history of cancer. Although these results require replication before becoming actionable in a clinical setting, they suggest the need for more rigorous examination of the effect of antihypertensive choice on long‐term cardiac outcomes in cancer survivors. Implications for Practice: Although additional research is needed to replicate these findings, these data from a large, nationally representative sample of postmenopausal women indicate that beta blockers are favorable to angiotensin‐converting enzyme inhibitors in reducing the risk of cardiac events among cancer survivors. This differs from the patterns observed in a noncancer cohort, which largely mirrors what is found in the randomized clinical trials in the general population. Abstract : This article analyzes long‐term cardiovascular outcomes in the Women's Health Initiative study to estimate the associations between incidental use of anti‐hypertensive medications and long‐term CVD outcomes in women with and without cancer.